Measurement of bronchial hyperreactivity: comparison of three Nordic dosimetric methods - Lassmann-Klee, Paul G.; Sundblad, Britt-Marie; Malmberg, Leo P.; Sovijärvi, Anssi R. A.; Piirilä, Päivi (SCANDINAVIAN JOURNAL OF CLINICAL & LABORATORY INVESTIGATION, 2020)
Clinical testing of bronchial hyperreactivity (BHR) provides valuable information in asthma diagnostics. Nevertheless, the test results depend to a great extent on the testing procedure: test substance, apparatus and protocol. In Nordic countries, three protocols predominate in the testing field: Per Malmberg, Nieminen and Sovijärvi methods. However, knowledge of their equivalence is limited. We aimed to find equivalent provocative doses (PD) to obtain similar bronchoconstrictive responses for the three protocols. We recruited 31 patients with suspected asthma and health care workers and performed BHR testing with methacholine according to Malmberg and Nieminen methods, and with histamine according to Sovijärvi. We obtained the individual response-dose slopes for each method and predicted equivalent PD values. Applying a mixed-model, we found significant differences in the mean (standard error of mean) response-dose (forced expiratory volume in one second (FEV 1 )%/mg): Sovijärvi 7.2 (1.5), Nieminen 13.8 (4.2) and Malmberg 26 (7.3). We found that the earlier reported cut-point values for moderate BHR and marked BHR between the Sovijärvi (PD 15 ) and Nieminen (PD 20 ) methods were similar, but with the Malmberg method a significant bronchoconstrictive reaction was measured with lower PD 20 values. We obtained a relationship between slope values and PD (mg) between different methods, useful in epidemiological research and clinical practice.